MOBILE ASISTEN KEHAMILAN BERBASIS ANDROID - Venny Enrizal; Yasdinul Huda; Dony Novaliendry (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
Pregnancy is a precious moment which is awaited by any married couples. Most people think that a marriage without children is not perfect. In the other hand, nine months of pregnancy is not an easy thing to get through, especially for the first pregnancy. So many changes happen to the mother along the pregnancy period. The deficient of knowledge and the lack of information about pregnancy become obstacle for the mothers-to-be to go through a period of their pregnancy. Utilizing the advance of science and communication technology nowadays, we can get various information about pregnancy easily. With the availability of mobile pregnancy assistant software based on android with file capacity 2mb for installation so that  not become a handicap for the devices. User, especially pregnant women can get information about pregnancy age,  estimation of birth  , pregnancy information, pregnancy tips and Islamic name choice provided in the mobile pregnancy assistant. This software is installer which operating in Android platform version 2.2 (Froyo) with Java programming language, built using Eclipse as IDE. Keyword: Pregnancy, Mobile Pregnancy Assistant, Android, Eclipse, Playstore